Workshop Kepemimpinan Digital Dalam Meningkatkan Kemampuan Komunikasi Pada PAC Fatayat NU Pinang - Aziz, Abdul; Emeilia, Rindana Intan; Muntazah, Arina; Andhikasari, Rosiana (CV. ITTC INDONESIA, 2024)
The emergence of the digital era and Industry 4.0 has brought a paradigm shift in understanding and practicing leadership. This concept is known as ‘digital leadership,’ emphasizing the importance of adapting to information technology and communication developments. The community service partner in this case is the Branch Leader (Pimpinan Anak Cabang or PAC) of Fatayat NU Pinang, located at Jl. M. Jali RT 02/03, Kunciran Jaya Subdistrict, Pinang City, Tangerang 15153. Fatayat NU Pinang is a community service partner classified as economically and socially non-productive. Their routine activities typically involve education, training, and religious social activities. Based on this context, the Faculty of Communication and Language at Universitas Bina Sarana Informatika will conduct a community service activity titled ‘Digital Leadership Workshop to Enhance Communication Skills for PAC Fatayat NU Pinang.’ The choice of this title is based on the challenges faced by the partner: (a) limited knowledge and understanding of digital leadership concepts, and (b) limited skills and abilities in using digital media as an organizational communication channel. The proposed solutions to address these challenges include: (a) providing workshop materials on basic digital leadership concepts, and (b) conducting a workshop on practical usage of Zoom meetings as a communication tool. The planned activity involves simulation sessions, optimizing Zoom features such as screen sharing, breakout rooms, polling, and chat. The expected outcomes of this community service project are articles in local electronic media and an increase in participants’ knowledge, understanding, skills, and abilities related to digital leadership and communication.